Desenvolvimento de meios de cultura de baixo custo para Ankistrodesmus gracilis à base de fertilizante inorgânico e macrófita - Sipaúba-Tavares, Lúcia Helena [UNESP]; Segali, Alexandra Maria Donadon Lusser [UNESP]; Berchielli-Morais, Flavia Almeida [UNESP]; Scardoeli-Truzzi, Bruno [UNESP] (FapUNIFESP (SciELO), 2017)
Aim: The influence of three different culture media on the growth and biochemical composition of Ankistrodemsus gracilis microalgae is evaluated. Methods: Microalgae were placed in a bath culture during 28 days, with inorganic fertilizer (NPK) and macrophyte Eichhornia crassipes as culture medium to compare the growth of microalgae and commercial medium CHU12. Protein and lipid contents, water conditions of the culture medium and physiological parameters were assessed weekly. Results: Growth rate, macro-minerals, micro-nutrients and nutritional values were similar to commercial culture medium in the media with inorganic fertilizer and macrophyte. The biological indexes of microalgae were not influenced by weekly differences during the study period. Although lipid contents, nitrogen and growth rate of A. gracilis were higher in inorganic fertilizer and macrophyte media; Mn, B, Cu, S, dry matter, ash content, cell volume, TOC and total length were similar among the media used. The same high cell density 25 x 105cells.mL-1was obtained in NPK and in CHU12medium respectively after 11 and 14 days cultivation. Conclusion: Culture media inorganic fertilizer (NPK) and macrophyte (Eichhornia crassipes), were adequate and may replace the commercial medium CHU12for the cultivation of microalgae A. gracilis, resulting in high nutritional composition, high biomass, high nutrients and low-cost.
Development of low-cost culture media for Ankistrodesmus gracilis based on inorganic fertilizer and macrophyte
Keywords: Biochemical composition; Culture media; Eichhornia crassipes; NPK (20-5-20)